A phase 1 randomized study of hemodynamic effects and pharmacokinetic interactions during concomitant use of rimegepant and sumatriptan in healthy adults. (28th April 2021) - Croop, Robert; Ivans, Andrea; Anderson, Matt S; Stringfellow, Joseph; Bertz, Richard; Hanna, Michael; Healy, Francine; Stock, David A; Coric, Vladimir; Lipton, Richard B
Objective: This randomized, partially-blinded, placebo-controlled study evaluated hemodynamic effects, pharmacokinetic interactions, and safety of concomitant administration of oral rimegepant and subcutaneous sumatriptan. Methods: Healthy non-smokers aged ≥18 and ≤40 years (men) or ≥18 and ≤50 years (women) were enrolled. On Day 1, subjects received 12 mg of sumatriptan as 2 subcutaneous 6 mg injections separated by 1 hour. From Days 2 to 4, subjects received rimegepant or placebo once daily (randomized 6 to 1, rimegepant to placebo). On Day 5, subjects received rimegepant or placebo, followed 2 hours later by 2 subcutaneous 6 mg injections of sumatriptan, separated by 1 hour. Sumatriptan was administered at the same times as on Day 1. Results: All 42 dosed subjects were analyzed. There were no significant differences in the time-weighted average of mean arterial pressure, diastolic blood pressure, or systolic blood pressure between treatment with rimegepant + sumatriptan and sumatriptan alone. Co-administration of rimegepant and sumatriptan had no effect on the pharmacokinetics of either drug. Overall, 93% (39/42) of subjects experienced ≥1 adverse event; injection site reaction was most common (60% [29/42]). Conclusions: Concomitant administration of oral rimegepant and subcutaneous sumatriptan to healthy adults was without hemodynamic or pharmacokinetic interaction and was safe and well tolerated.